An Analysis of the Associations among Cognitive Impulsiveness, Reasoning Process, and Rational Decision Making - Jelihovschi, Ana P. G.; Cardoso, Ricardo L.; Linhares, Alexandre (Frontiers in Psychology, 2018)
Impulsivity may lead to several unfortunate consequences and maladaptive behaviors for both clinical and nonclinical people. It has a key role in many forms of psychopathology. Although literature has discussed the negative impact of impulsivity, few have emphasized the relationship between cognitive impulsiveness and decision making. The aim of this study is to investigate the effects of cognitive impulsiveness on decision making and explore the strategies used by participants to solve problems. For this purpose, we apply two measures of impulsivity: the self-report Barratt Impulsiveness Scale (BIS-11) and the performance-based Cognitive Reflection Test (CRT). Moreover, we evaluate participants’ reasoning processes employed to answer CRT questions based on the calculation expressions, data organization, and erasures they made while answering the CRT (note that we utilized the instruments using pen and paper). These reasoning processes are related to the role of executive functions in decision making, and its relationship with impulsiveness. The sample consists of 191 adults, who were either professionals or undergraduate students from the fields of business, management, or accounting. The results show that cognitive impulsiveness may negatively affect decision making, and that those who presented the calculation to answer the CRT questions made better decisions. Moreover, there was no difference in the strategies used by impulsive versus nonimpulsive participants during decision making. Finally, people who inhibited their immediate answers to CRT questions performed better during decision making.